LEAVING AGAINST MEDICAL ADVICE IN PAEDIATRIC UNIT OF AMINU KANO TEACHING HOSPITAL, KANO, NIGERIA - SI ADELEKE; MO ASANI; RO BELONWU; YM MUHKTAR (Ntec Specialist, 2001)
Background: Children are vulnerable and cannot make decisions about their health care. There are many cases of parents leaving against medical advice (LAMA) and this can lead to adverse health problems in the children. Objective: The study was aimed at determining the prevalence of, and factors associated with, leaving against medical advice at the Paediatric Unit of the Aminu Kano Teaching Hospital, Kano. Methods: All patients who left against medical advice were included in the study. The study was a prospective one and information sought were age, sex, duration of hospital stay, socio-economic class of parents and reasons for leaving against medical advice over a five-year period (Jan. 2001 to Dec. 2005). Results: Prevalence rate of LAMA was 2.2%, comprising 68 patients of 3,095 discharges, HIV/Pulmonary tuberculosis 17(23%) were the commonest causes of admission in the group of patients aged (10months-12years). Seventy-five percent of the patients were discharged within two weeks of admission. Sixty patients (88.2%) belonged to the lower soci-economic class. Conclusion: LAMA has multifactorial aetiololgy. Low social economic class, poor financial support and unpreparedness for hospital admission are risk factors